The Trigonometric Adaptive Worksheet Performance in Optimizing Trigonometric Thinking of Prospective Mathematics Teacher: Single Subject Research - Usep Sholahudin; Rina Oktaviyanthi (Universitas Syiah Kuala, 2023)
The ability to think in trigonometry supports the understanding of trigonometry concepts, which still pose challenges for first-year university students, including prospective teachers. The Trigonometric Adaptive Worksheet is one of the student worksheets to optimize trigonometric thinking abilities. This research aimed to assess the performance of the Trigonometric Adaptive Worksheet on the trigonometric thinking abilities of prospective mathematics teachers. Quantitative descriptive research with a Single Subject Research method and a basic design of A (baseline) - B (intervention) was employed as the research approach. Three prospective mathematics teachers from three categories of high, moderate, and low mathematical abilities were selected as research subjects. The data related to changes in individual behavior regarding progress in trigonometric thinking abilities were analyzed using within-condition analysis and between-condition analysis procedures. Based on the single-subject data analysis of the three research subjects, it is evident that moderate and low subjects tend to benefit more from implementing the Trigonometric Adaptive Worksheet. These findings have important implications, suggesting adaptive worksheets can enhance individual learning outcomes by tailoring content to individuals' needs. The worksheet adaptability and personalization provide an opportunity to improve trigonometry instruction's effectiveness.